Intervention plan for the protection of APPs: case study of the Espinharas River in the city of Patos - PB - Silva, Emmanoel Marques da; Albuquerque, Sheila Rodrigues de; Carvalho, Gabriel Lincoln Lopes; Silva, Paulo Roberto de Oliveira; Silveira, José Augusto Ribeiro da (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Due to the urbanization processes of recent years, a significant loss of the relationship between water resources and cities has been observed, where Areas of Permanent Preservation (APPs) have been gradually degraded and irregularly occupied. Given these scenarios, laws such as the Forest Code (Federal Law No. 12,651/2012) have been created in an attempt to mitigate and preserve the riparian zones of rivers, mangroves, lakes, ponds, and other water bodies, but due to problems in the applicability of the law itself. Thus, this study proposed to study the PPAs of the Espinharas River in the city of Patos/PB, to highlight interventions that can generate requalification of the river banks. The method of analysis chosen was exploratory research, with the support of techniques such as field visits, photographic surveys, data collection, mapping of PPAs, and finally the diagnosis of land use and watershed. The results of this study consisted of the proposal of a linear park plan applied in the areas of the PPAs of the Espinharas River, urban equipment that has the purpose of providing the requalification, restoration, and renaturalization of the areas degraded by the processes of irregular occupation and urbanization.